2021
DOI: 10.15414/jmbfs.4232
|View full text |Cite
|
Sign up to set email alerts
|

A New Role of Metformin as an Efflux Pump Inhibitor in Klebsiella Pneumonia

Abstract: Respiratory tract infections caused by Klebsiella pneumoniae are frequently associated with high mortality and morbidity rates. Treatment of these infections is usually difficult due to the emergence of multiple resistances to antibiotics. Multidrug efflux pumps are greatly involved in antibiotic resistance in Gram-negative bacteria including Klebsiella pneumoniae. In the current study, efflux activity was observed in 93.75% of Klebsiella pneumoniae clinical isolates by the qualitative acridine orange agar met… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 33 publications
0
9
0
Order By: Relevance
“…Furthermore, Baiomy et al [64] study tested the EPI activities by two methods; EtBr-Cartwheel method and determining the decrease in the antibiotics MICs, while, our study used four methods in which our results were confirmed by RT-PCR unlike Baiomy et al [64] study. In another study; Abbas et al [73] study, metformin significantly reduced tetracycline and ciprofloxacin MICs in MDR of Klebsiella pneumonia isolates.…”
Section: Plos Onementioning
confidence: 86%
See 2 more Smart Citations
“…Furthermore, Baiomy et al [64] study tested the EPI activities by two methods; EtBr-Cartwheel method and determining the decrease in the antibiotics MICs, while, our study used four methods in which our results were confirmed by RT-PCR unlike Baiomy et al [64] study. In another study; Abbas et al [73] study, metformin significantly reduced tetracycline and ciprofloxacin MICs in MDR of Klebsiella pneumonia isolates.…”
Section: Plos Onementioning
confidence: 86%
“…Thus, the repurposing of the drugs as the FDA-approved ones as it saves the costs and shortens the long time needed for the development of new antimicrobials [68]. This concept has been applied recently in many studies [59,64,[69][70][71][72][73][74].…”
Section: Plos Onementioning
confidence: 99%
See 1 more Smart Citation
“…ENT646 is a hypervirulent K. pneumoniae (hvKp) isolate, [38] an example of the alarming emergence of "superbugs" due to the increasing convergence of hypervirulence and carbapenem resistance in K. pneumoniae. [38][39][40] The initial pool of 12 drugs was selected from three groups: 1) mainstay antibiotics essential for treating CRE infections, such as MEM and polymyxin B (PB); [8,9,41] 2) drug sensitizers, such as efflux pump inhibitor metformin; [42] and 3) repurposed drugs reported with antibacterial activity (Table 1). IDentif.AI assesses three clinically relevant drug concentrations.…”
Section: Two Selected Cre Strains 12 Fda-approved Drugs and Drug Conc...mentioning
confidence: 99%
“…Grimsey et al 67 demonstrated the efficacy of chlorpromazine and amitriptyline as EPIs to restore the antibacterial activity of the given antibiotics and inhibit the AcrB-mediated efflux. Abbas et al 68 investigated the potential inhibition activity of novel EPI (metformin) on AcrAB and Mdtk efflux pumps of K. pneumoniae. Their reports suggest the use of metformin over the existing EPIs ascorbic acid and verapamil in restoring the efficacy of the antibiotics.…”
Section: Efflux Pump Inhibitorsmentioning
confidence: 99%